Effects of alcohols on interfacial tension between carbon dioxide and crude oil at elevated pressures and temperature - Moradi, B. (Elsevier, 2014)
A laboratory study was conducted to investigate the effects of alcohols on interfacial tension (Î³) between crude oil and carbon dioxide by the pendant drop method over pressures up to 16.55 MPa and at 375.15 K. Simultaneously, the density of fluids was measured as the data were required for the calculation of Î³. The linear, branched, and mixed alcohols were used at concentrations (0, 2.5, 5, and 10) by volume. Analysis of results revealed that moving from linear to branched alcohols results in higher Î³ reduction. However, branching of alcohols for reducing the Î³ was only effective up to a certain carbon chain length after which, increasing the carbon chain length or branches have no effect on Î³ reduction. Furthermore, it was revealed that Î³ reduction for different concentrations of alcohols were approximately equal at high pressure (â16.55. MPa), thus lower concentration of the alcohols was suggested to be used to reduce the project cost of enhanced oil recovery in high pressure reservoirs. Â© 2014 Elsevier B.V.